Abdominal perimeter is the best anthropometric risk indicator of cardiovascular diseases - Maria Fátima Glaner; Andreia Pelegrini; Thales Boaventura Rachid Nascimento (Universidade Federal de Santa Catarina, 2011)
The objectives of this study were: a) to determine the prevalence of inadequate body fat determined based on body mass index (BMI), abdominal perimeter (AP) and relative body fat (%F), and biochemical indicators of cardiovascular risk, and b) to examine which body fat indicators better reflect the biochemical factors. BMI, %F, AP, glucose, triglycerides, total cholesterol, high-density lipoprotein (HDL), and low-density lipoprotein (LDL) were measured in 125 men. More than half the sample (56.8%) had low HDL and high BMI (58.4%) and %F (53.6%). There was a lower percentage of subjects with elevated LDL (40.8%), AP (38.4%), triglycerides (34.8%), glucose (27.2%), and total cholesterol (15.2%). AP was associated with four biochemical markers, whereas %F was associated with three and BMI with only two. The prevalence of risk factors was high. An AP >92 cm proved to be the best fat indicator, demonstrating that men are exposed to high levels of LDL, total cholesterol, triglycerides, and glucose.